The HeKatE methodology. Hybrid engineering of intelligent systems - Nalepa, Grzegorz J.; Ligęza, Antoni (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes a new approach, the HeKatE methodology, to the design and development of complex rule-basedsystems for control and decision support. The main paradigm for rule representation, namely, eXtended Tabular Trees(XTT), ensures high density and transparency of visual knowledge representation. Contrary to traditional, flat rule-basedsystems, the XTT approach is focused on groups of similar rules rather than on single rules. Such groups form decisiontables which are connected into a network for inference.
Keywords: rule-based expert systems; intelligent control; system design